Answer: the answer is a
Step-by-step explanation: i did all the work that i could do on my paper
Just add them
QM+MR=QR
16+x+2(x+2)=QR
16+x+2x+4=QR
20+3x=QR
The third term of the expansion is 6a^2b^2
<h3>How to determine the third term of the
expansion?</h3>
The binomial term is given as
(a - b)^4
The r-th term of the expansion is calculated using
r-th term = C(n, r - 1) * x^(n - r + 1) * y^(r - 1)
So, we have
3rd term = C(4, 3 - 1) * (a)^(4 - 3 + 1) * (-b)^(3-1)
Evaluate the sum and the difference
3rd term = C(4, 2) * (a)^2 * (-b)^2
Evaluate the exponents
3rd term = C(4, 2) * a^2b^2
Evaluate the combination expression
3rd term = 6 * a^2b^2
Evaluate the product
3rd term = 6a^2b^2
Hence, the third term of the expansion is 6a^2b^2
Read more about binomial expansion at
brainly.com/question/13602562
#SPJ1
Answer:
15.1 to nearest tenth.
Step-by-step explanation:
The 7 is the lowest number so the mean would increase if taken away.
New mean = (8 + 12 + 13 + 15 + 18 + 19+21) / 7
= 106 / 7
= 15.14
Answer:
f=7x g=3 x=18
Step-by-step explanation: